48 A new course development – european trauma course. (17th November 2016) - Major, D; Clappison, E; Peck, J; Griscti, R; Purva, M
Abstract : Due to the current financial climate amongst the NHS, HILS realise the need to work towards becoming self-sufficient financially. One way to assist in achieving this goal is by attracting new courses to be developed and delivered at HILS. Lessons learned in how to attract and deliver a successful course will be shared with the intention that it will be a useful resource for both new and existing centres. Courses need to be booked into the planned venue as soon as possible. Due to ETC requiring 4 consecutive days and the whole centre to run, HILS had availability in March 2016 – 12 months into the future. The course and dates were registered for approval with the European Resus Council (ERC), once this was granted the course dates were advertised through the ERC website. Dr Griscti (Co-Director) then began recruiting faculty 12 months prior to the course taking place as 12 faculty members were needed along with a Director, Co-Director and an Educator. The course was then widely advertised following creating a poster for the course. 6 months prior to the course taking place, HILS observed ETC taking place in Birmingham. This was highly beneficial as it helped the team appreciate the scale of the course when planning for it. Knowing the course format allowed the team to plan which stations would run in each room. Issues arose in terms of a lack of equipment available, the team worked hard with to allocate items available within the Trust. Impact: Successful course ran March 2016, positive feedback Income generated Next course booked November 2016 ETC has helped HILS attract a hospital trauma course to run within the facility Delegates evaluations (1 = poor 4 = excellent) resulted the first course being all rated 3.6 and above.